Music Augmented With Isochronic Auditory Beats or Vibrotactile Stimulation Does Not Affect Subsequent Ergometer Cycling Performance: A Pilot Study - Fry, Adam; Braren, Stephen; Pitaro, Nicholas; Larson, Brandon; Putrino, David (Frontiers in Human Neuroscience, 2021)
Methods to enhance the ergogenic effects of music are of interest to athletes of all abilities. The aim of this pilot study was to investigate the ergogenic effects of two commercially available methods of music augmentation: auditory beats and vibrotactile stimulation. Six male and five female cyclists/triathletes cycled for 7 minutes at three different intensities: a rate of perceived exertion (RPE) of 11 (“light”), RPE of 15 (“hard”), and a 7-minute time-trial. Before each 7-minute bout of cycling, participants listened to 10 minutes of self-selected music (MUS), or the same music with the addition of either isochronic auditory beats (ABS) or vibrotactile stimulation via SUBPACTM (VIB). MUS, ABS and VIB trials were performed in a randomized order. Power output was measured during cycling and felt arousal and feeling scores were recorded at timepoints throughout the protocol. The results found the augmented MUS interventions did not influence power output with no significant main effect of trial (p = 0.44, η2 = 0.09) or trial × cycling intensity interaction (p = 0.11, η2 = 0.20). Similarly, both felt arousal and feeling scores were unchanged between the MUS, ABS, and VIB trials (p > 0.05). In conclusion, this pilot study indicated an ineffectiveness of the ABS and VIB to affect subsequent 7-min cycling performance compared to self-selected MUS alone.